2009
DOI: 10.1007/s00018-009-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelets in the pathogenesis of cerebral malaria

Abstract: Malaria is a major cause of morbidity and mortality in the developing world and cerebral malaria is responsible for the majority of malaria-associated deaths. There is a strong association between thrombocytopenia and outcome in malaria, suggesting a role for platelets in the pathogenesis of malaria. This thrombocytopenia is likely due to platelet activation possibly through an interaction between PfEMP1 on plasmodium and CD36 on platelets. Platelet activation by plasmodium has two potential consequences. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 119 publications
3
78
1
1
Order By: Relevance
“…12,66 The mechanisms responsible for this thrombocytopenia have not been fully elucidated, but a number of putative mechanisms have been proposed. 66,67 In addition, a series of studies dating back to the 1960s have shown that coagulation cascade activation is also common in both children and adults with P falciparum infection.…”
Section: Coagulation Cascade Activation In Malariamentioning
confidence: 99%
“…12,66 The mechanisms responsible for this thrombocytopenia have not been fully elucidated, but a number of putative mechanisms have been proposed. 66,67 In addition, a series of studies dating back to the 1960s have shown that coagulation cascade activation is also common in both children and adults with P falciparum infection.…”
Section: Coagulation Cascade Activation In Malariamentioning
confidence: 99%
“…CD36, a platelet receptor for infected erythrocytes, is also present in brain endothelium and may play a role in platelet activation. However, the exact mechanism for thrombocytopenia is not known [24].…”
Section: Discussionmentioning
confidence: 99%
“…Rosetting pRBCs bind to the endothelial cells and occlude microvessels in the brain (Cox and McConkey 2010). Therefore, it is not surprising that thrombocytopenia is a common feature in both murine ECM and human CM (Wassmer, Combes et al 2003;Combes, ElAssaad et al 2010).…”
Section: Plateletsmentioning
confidence: 99%
“…Interactions between PfEMP1 on Plasmodium and CD36 on platelets possibly lead to platelet activation. The platelet activation aggregates pRBCs and platelets resulting in occlusion of microcirculation and activation of the endothelial cells (Cox and McConkey 2010). gC1qR/HABP/p32 interacts with both pRBCs and platelets potentiating clumping of pRBCs (Biswas, Hafiz et al 2007).…”
Section: Plateletsmentioning
confidence: 99%
See 1 more Smart Citation